LANGUAGE AS A SEMIOTIC SYSTEM - Mehdiyeva Aygun Elkhan (Scientific Research and Experimental Development, 2025)
The article deals with the science of signs, relationship between language and semiotics. Signs and the sign systems formed by them are studied by semiotics. In the development of this science, the foundations of which were laid by representatives of ancient and medieval philosophical thought, Charles Sanders Peirce, Charles William Morris, Ferdinand de Saussure, Louis Hjelmslev, Ernst Cassirer, Roman Osipovich Jakobson, Karl Buehler, Jakob von Uexcuell, Thomas Sebeok, Roland, Bart (Roland Barthes), Umberto Eco (Umberto Eco), Yury Stepanov